Prophets, Gurus, and Pundits : Rhetorical Styles and Public Engagement - Young, Anna M., 1975- (Book collections on Project MUSE., 2014)
In Prophets, Gurus, and Pundits, author Anna M. Young proposes that the difficulty of bridging the gap between intellectuals and the public is not a failure of ideas; rather, it is an issue of rhetorical strategy. By laying a rhetorical foundation and presenting analytical case studies of contemporary "public intellectuals," Young creates a training manual for intellectuals who seek to connect with a public audience and effect change writ large. Young begins by defining key aspects of rhetorical style before moving on to discuss the specific ways in which intellectuals may present ideas to a ge.